Qualitative Inherent Safety Assessment for Flammability Evaluation of Deep Eutectic Solvent (Journal of Energy and Safety Technology (JEST), 2023)
Due to the increasing demand for green and sustainable analytical methods, many researchers have been using various attempts to improve and design environmentally friendly chemical processes. Based on the literature, most of the researchers agreed that DESs is one of the attractive solutions to environmentally friendly chemicals due to its classification as a green solvent and safe to use due to its low flammability characteristic. Although studies on the benefits and advantageous implementation of DESs are extensive, investigation on the safety level of DESs is still lacking. This paper aims to introduce a simple qualitative inherent safety assessment method for flammability evaluation of DESs. Flash point values of the HBA and HBD component of DES are used in evaluating the flammability level of the DES. Subjective score assignment was utilized based on the flash point data as well as mixing temperature in the production of DES. In this scoring method, higher score represents higher flammability hazard. The resulted scoring method has five level of hazards representing five range of flash point values with 5 indicates the highest and most hazardous score while 1 is the lowest and the least hazardous score. Implementation on a simple case study shows that this scoring method is easy to use and can be easily improved for future usage as more safety information on DES emerge.
Keywords: Deep Eutectic Solvents; Flammability; Inherent Safety Assessment; Flash Point; Hydrogen Bond Acceptor; Hydrogen Bond Donor